The influence of elongation exercises on the anterior-posterior spine curvatures - Drzał-Grabiec Justyna; Snela Sławomir; Rykała Justyna; Podgórska Justyna; Truszczyńska Aleksandra (Sciendo, 2014)
Introduction: Elongation exercises are designed to reduce existing pathological or increased physiological curvatures of the spine. The aim of the study was to evaluate the changes occurring in the parameters describing the anterior-posterior spinal curvatures during the performance of symmetric elongation exercises.